Validity of the Chinese Mandarin version of the compassionate engagement and action scales for self and others for nursing students - Xianwei Wang; Qingfang Yao; Hu Jiang (BMC Nursing)
Abstract Background Compassion is a key concept in positive psychology. The value of compassion in hospital settings is evident. Three flows were used to gauge compassion. Nursing students have received less attention than other healthcare professionals regarding the various compassion-related scales available. Purpose This study aimed to adapt and validate a Mandarin Chinese edition of the Compassionate Engagement and Action Scales (CEAS) specifically for nursing students and to assess its psychometric characteristics. Methods The Hong Kong and original versions of the CEAS were combined to create the Chinese Mandarin version, which was then translated and culturally adjusted using a standard process. A non-probability sampling technique, specifically convenience sampling, was employed to recruit 428 nursing students to assess the validity and reliability of the measurement instrument from February to June 2024. Convergent, structural, and content validity were evaluated. Test-retest reliability and Cronbach’s alpha coefficient were used to assess reliability. Results The Chinese Mandarin version of the CEAS comprises three distinct dimensions, demonstrating high internal consistency with Cronbach’s alpha(McDonald’s Omega) values of 0.925(0.922), 0.938(0.936), and 0.932(0.930) for self-compassion, compassion towards others, and received compassion, respectively. The retest reliability was 0.992, 0.810, and 0.845 for these dimensions. Confirmatory factor analysis confirmed a well-fitting model, revealing satisfactory indices for self-compassion (χ2/df = 3.441, CFI = 0.980, GFI = 0.973, TLI = 0.968, IFI = 0.980, RMSEA = 0.076), compassion for others (χ2/df = 4.800, CFI = 0.971, GFI = 0.964, TLI = 0.956, IFI = 0.971, RMSEA = 0.084), and compassion from others (χ2/df = 4.913, CFI = 0.966, GFI = 0.958, TLI = 0.950, IFI = 0.966, RMSEA = 0.086). Conclusion The reliability and validity indicators of the CEAS’ Chinese Mandarin version meet the standards, making it a trustworthy tool for measuring nursing students’ compassionate engagement and action.